2013
DOI: 10.14233/ajchem.2013.13596
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Antimicrobial Activity of First Row Transition Metal(II) Complexes of Novel Schiff Base Derived from Sulfapyridine and Pyridine-2-Aldehyde

Abstract: A new Schiff base ligand (N-pyridin-2-yl-4-[(pyridin-2-yl)methyl amino]benzene sulfonamide) (L) was prepared by the reaction between sulfapyridine and pyridine-2-aldehyde. The ligand is bidentate by coordinating through pyridinyl nitrogen and azomethine nitrogen atom with Co(II), Ni(II), Cu(II), Zn(II) and Mn(II) chlorides. The complexes were synthesized and characterized by elemental analysis, molar conductance, magnetic moment, IR, H 1 NMR and electronic spectral data. These complexes were screened in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
1
0
0
Order By: Relevance
“…This band is shifted to a higher frequency (1649 cm −1 ) in the complex compared with those of the Schiff-base ligand showing the coordination of the imino-nitrogen 19 to the copper atom. This is further confirmed by the appearance of a new band at 410 cm −1 due to the ν(M-N) 20 band. The coordination through the phenolic oxygen after deprotonation is revealed by the disappearance of the ν(OH) phenolic band at 3504 cm −1 and the shift of phenolic ν(C-O) 21 …”
Section: Characterization Of Metal Complexsupporting
confidence: 52%
“…This band is shifted to a higher frequency (1649 cm −1 ) in the complex compared with those of the Schiff-base ligand showing the coordination of the imino-nitrogen 19 to the copper atom. This is further confirmed by the appearance of a new band at 410 cm −1 due to the ν(M-N) 20 band. The coordination through the phenolic oxygen after deprotonation is revealed by the disappearance of the ν(OH) phenolic band at 3504 cm −1 and the shift of phenolic ν(C-O) 21 …”
Section: Characterization Of Metal Complexsupporting
confidence: 52%
“…Previous studies were observed that the SPY is very much effective against the Bacillus subtillis and Staphylococcus aureus bacteria 5 . The stable chelate ring structure form by the nitrogen of the azomethine group and the nitrogen of the pyridinyl ring has stronger antimicrobial activity 6 . The related literature reported that SPY showed almost no loss of antimicrobial activity during hydrolysis 7 …”
Section: Introductionmentioning
confidence: 99%
“…5 The stable chelate ring structure form by the nitrogen of the azomethine group and the nitrogen of the pyridinyl ring has stronger antimicrobial activity. 6 The related literature reported that SPY showed almost no loss of antimicrobial activity during hydrolysis. 7 Hydrolysis was the most common reactions in pollution degradation.…”
mentioning
confidence: 99%